Czy orientacje życiowe studentów mediują relację między sumiennością jako cechą osobowości a osiągnięciami akademickimi? - Rękosiewicz, Małgorzata (Studia Edukacyjne, 2020)
Conscientiousness as a personality trait has been recognized as a predictor of students’ academic achievements in numerous empirical studies. The aim of the study was to determine the role of life orientations, moratorium and transitive orientation, in the relationship between conscientiousness and academic achievement. The study was conducted using Social Participation Questionnaire and the NEO-FFI Personality Inventory among 111 full-time students aged 20-25. Conscientiousness turned out to be a predictor of both academic achievement and life orientation, but these orientations did not mediate the relationship between conscientiousness and academic achievement.